Creative Thinking Process of Kinesthetic Male Students in Solving Mathematics Problems in Elementary School - Ishabu, La Suha; Nugroho, Aryo Andri (Jurnal Pendidikan MIPA, 2024)
Various concepts have been introduced in every lesson to improve students' mathematical analytical ability. This paper introduces a new concept to improve students' creative thinking ability based on kinesthetic learning style in solving math problems. The uniqueness of Kinesthetic male students' creative thinking process in elementary school can be seen when a person can solve problems correctly, use accurate and different approach strategies, create the correct solution process, and produce unique and new products. The primary purpose of this research is to describe the uniqueness of Kinesthetic male students' creative thinking process in solving mathematics problems in elementary school. The method used in this study is qualitative. The subjects in this study were fifth-grade students of SD Negeri 7 Dobo, Aru Islands Regency. The instrument used in this study was a student creativity test on geometry. This research resulted in a valuable lesson that Male Subjects with Kinesthetic Learning Styles have different uniqueness in solving mathematics. The discovery of correct ideas can prove this by presenting more than one different and correct approach and solution strategy and the discovery of a correct and unique (unusual) answer completed by kinesthetic male students at their stage of development or level of knowledge.         Keywords: uniqueness of creative thinking process, mathematical problem solving, male subject, kinesthetic learning style. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp313-328